Development of a Novel Chimeric ND-GP cVLPs Vaccine for the Prevention of Goose-Derived Newcastle Disease and Gosling Plague - Jindou Li; Jiaxin Ding; Chunhong Guo; Xiaohong Xu; Chunhui Shan; Jing Qian; Zhuang Ding (Microorganisms, 2024)
Goose-derived Newcastle disease (ND) and gosling plague (GP) are serious threats to the goose industry. Conventional vaccines have made significant contributions to preventing GP and ND. Nevertheless, the renewal of conventional vaccines and the application of novel vaccines are urgently needed to align with eco-friendly and efficient breeding concepts and achieve the final goal of epidemic purification. Therefore, based on the Newcastle disease virus-like particles (ND VLPs) vector platform, we developed novel chimeric ND-GP bivalent cVLPs (ND-GP cVLPs) displaying the NDV HN protein and the GPV VP3 protein. In vivo, immunization experiments revealed that geese immunized with 30 µg, 50 µg, or 70 µg of the ND-GP cVLPs and commercial vaccines produced highly effective hemagglutination inhibitory antibodies against NDV and neutralizing antibodies against GPV, respectively. Furthermore, 70 µg of the ND-GP cVLPs effectively protected against virulent NDV and GPV, reducing tissue damage from viral infection and virus shedding in the oropharynx and cloaca. In conclusion, we provide eco-friendly and efficient novel ND-GP cVLPs for preventing goose-derived ND and GP. Our findings provide the basis for using ND VLPs as foreign protein carriers for the developing of multi-conjugate vaccines.